Household Welfare of Corn Farmers: A Maqashid Syariah Perspective (Case Study of Ipar Bondar, Panyabungan, Mandailing Natal) - Sapna Katmila; Setiadi, Dr. Iwan (Cita konsultindo, 2024)
Welfare based on Maqashid Syariah refers to efforts to achieve the primary objectives of Sharia, which are to preserve and protect five aspects of human life: Hifz ad-din, Hifz an-Nafs, Hifz al-'Aql, Hiz an-Nasl, and Hifz al-Mal, while also conducting corn farming in accordance with Sharia financial principles, including syar'i and tabi'i principles. The aim of this research is to provide a deeper understanding of the welfare of corn farmers from the Maqashid Syariah perspective. This study employs a qualitative research method using a grounded theory model. The findings reveal that farmers in Saba, Ipar Bondar Village, achieved higher welfare levels when cultivating rice compared to corn, based solely on material financial assessments. However, by integrating Sharia financial principles and Maqashid Syariah into farming activities and family life, the farmers were able to create holistic and sustainable welfare that brought blessings and goodness to all members of the household.